EKSISTENSI PCNU KOTA SERANG SEBAGAI INSTRUMEN DAKWAH DAN PEMBANGUNAN SOSIAL - Silmi Nurpadilah; Muhamad Afandi Hafiz Ali; Nurul Hasan zafira; Shofa Fadhilah Almusyarofah; Siti umiyatunupus; Intan maharani; Mujtahid Baehaqi; Azkia sabili; Anah Maimanah; Nurhasanah; Safiroh Febriani; Putri Indah Permata Sari; Fikri; Tazkia Nasiha; Anas Tasya Marisa Haryani; Fadella Kalinda Abdul; Fauzan Akmal Fatahillah; Tb Nurwahyu (STKIP Subang, 2026)
This study aims to analyze the existence of the Serang City Branch Executive Board of Nahdlatul Ulama (PCNU) as an instrument of Islamic da'wah and social development. This research employed a qualitative method using interviews, observations, and documentation as data collection techniques. The results show that PCNU Serang City plays an active role in strengthening Ahlussunnah wal Jama'ah values through religious activities, education, cadre development, and digital da'wah. Furthermore, PCNU contributes to social development through community empowerment programs, economic strengthening, humanitarian activities, and collaboration with local government. The Bahtsul Masail program serves as a forum for addressing religious and social issues within society. Therefore, PCNU Serang City functions not only as a da'wah organization but also as an agent of social development that promotes Islamic, national, and social values.